ASPECTS OF THE VOCAL-SYMPHONIC GENRE - GHIŞA, Lucian (Studia Universitatis Babes-Bolyai Musica, 2011)
The vocal-symphonic genre is expressed by employing an apparatus that includes the orchestra, the choir and the soloists. It is to be found in several instances: the musical theatre – opera; without means of theatrical expression – oratorio, and cantata. The borderline between oratorio and cantata is placed in embracing lyrical and epical aspects – in the case of the cantata – or dramatic – in the case of the oratorio. The oratorio is divided in two categories according to the text: the secular and religious oratorio. The religious oratorio has several subgenres given by the use of a pre-established text: Requiem, Mass, Passion, Te Deum, Stabat Mater, and others.